Feasibility of Vascular Endothelial Growth Factor Imaging in Human Atherosclerotic Plaque Using Zr-Bevacizumab Positron Emission Tomography - Reza Golestani; Clark J. Zeebregts; Anton G.T. Terwisscha van Scheltinga; Marjolijn N. Lub-de Hooge; Gooitzen M. van Dam; Andor W.J.M. Glaudemans; Rudi A.J.O. Dierckx; René A. Tio; Albert J.H. Suurmeijer; Hendrikus H. Boersma; Wouter B. Nagengast; Riemer H.J.A. Slart (Molecular Imaging)
Intraplaque angiogenesis is associated with the occurrence of atherosclerotic plaque rupture. Cardiovascular molecular imaging can be used for the detection of rupture-prone plaques. Imaging with radiolabeled bevacizumab, a monoclonal anti-vascular endothelial growth factor (VEGF)-A, can depict VEGF levels corresponding to the angiogenic status in tumors. We determined the feasibility of 89 Zr-bevacizumab imaging for the detection of VEGF in carotid endarterectomy (CEA) specimens. Five CEA specimens were coincubated with 89 Zr-bevacizumab and aspecific 111 In-labeled IgG to determine the specificity of bevacizumab accumulation. In 11 CEA specimens, 89 Zr-bevacizumab micro-positron emission tomography (PET) was performed following 2 hours of incubation. Specimens were cut in 4 mm wide segments and were stained for VEGF and CD68. In each segment, the mean percent incubation dose per gram of tissue (%Inc/g) and tissue to background ratio were determined. A 10-fold higher accumulation of 89 Zr-bevacizumab compared to 111 In-IgG uptake was demonstrated by gamma counting. The mean %Inc/g hot spot was 2.2 ± 0.9 with a hot spot to background ratio of 3.6 ± 0.8. There was a significant correlation between the segmental tissue to background uptake ratio and the VEGF score (ρ = .74, p < .001). It is feasible to detect VEGF tissue concentration within CEA specimens using 89 Zr-bevacizumab PET. 89 Zr-bevacizumab accumulation in plaques is specific and correlates with immunohistochemistry scores.